2021
DOI: 10.3389/fpsyg.2021.764434
|View full text |Cite
|
Sign up to set email alerts
|

Social Identity, Perceived Emotional Synchrony, Creativity, Social Representations, and Participation in Social Movements: The Case of the 2019 Chilean Populist Protests

Abstract: This paper analyzes the socio-cognitive and emotional processes related to collective action in the context of the 2019 populist social movement in Chile. It proposes an integrative explanation of populism as social movements and collective gatherings along with their relation with creativity and social representations of mass movements. A comprehensive online survey was used (n = 262) that included measures of participation in demonstrations, identification with protesters or the government, agreement with so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 41 publications
1
12
0
Order By: Relevance
“… Morales (2020) , for instance, suggests that a social outbreak of these characteristics was foreseeable, as the country was in the grip of four significant crises: (1) a crisis of participation—exacerbated by voluntary voting since 2012, (2) a crisis of representation, that is, lower adherence to political parties and loss of confidence in key democratic institutions (e.g., government, courts, and congress), (3) a crisis of trust in public institutions and those related to social order (e.g., police, the church), and finally, (4) a crisis of probity, with frequent cases of irregular funding of politics and business collusions. In a similar vein, a recent study also points to the lack of trust and confidence in municipal political institutions and a general misidentification with the elite and the government, as factors leading to the outbreak ( Castro-Abril et al, 2021 ). Particularly, analyzes of nationally representative survey data on Chilean adults from 2015 to 2019 suggested that perceived corruption in key institutions (e.g., parliament, army, police, municipalities, churches, congress, courts of justice, political parties, and even in sports organizations) significantly increased during the 6-year period observed ( Moyano-Díaz et al, 2021 ).…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“… Morales (2020) , for instance, suggests that a social outbreak of these characteristics was foreseeable, as the country was in the grip of four significant crises: (1) a crisis of participation—exacerbated by voluntary voting since 2012, (2) a crisis of representation, that is, lower adherence to political parties and loss of confidence in key democratic institutions (e.g., government, courts, and congress), (3) a crisis of trust in public institutions and those related to social order (e.g., police, the church), and finally, (4) a crisis of probity, with frequent cases of irregular funding of politics and business collusions. In a similar vein, a recent study also points to the lack of trust and confidence in municipal political institutions and a general misidentification with the elite and the government, as factors leading to the outbreak ( Castro-Abril et al, 2021 ). Particularly, analyzes of nationally representative survey data on Chilean adults from 2015 to 2019 suggested that perceived corruption in key institutions (e.g., parliament, army, police, municipalities, churches, congress, courts of justice, political parties, and even in sports organizations) significantly increased during the 6-year period observed ( Moyano-Díaz et al, 2021 ).…”
Section: Introductionmentioning
confidence: 92%
“…It has been suggested that different factors underlie the social outbreak, including a long-standing anomic process ( Moyano-Díaz et al, 2021 ), and the dominant neoliberal socioeconomic model and its consequences (i.e., neoliberalism; Garretón, 2021 ). These include inequalities, and, particularly, the irritation of those who feel marginalized and exploited ( Castro-Abril et al, 2021 ) and whose dignity has been wounded. Different explanations have been proposed—although most are ideological or political rather than empirical—regarding the reasons that led to the social outbreak of 2019.…”
Section: Introductionmentioning
confidence: 99%
“…One longitudinal study found that youth with high online and offline participation in the Umbrella SM 2014 in Hong Kong showed significantly higher levels of psychological and social wellbeing, higher leadership competence and political control, as well as lower perceptions of government responsiveness during the period of street occupation. In the year after the movement, youth with high participation had a significant decline in psychological and social wellbeing compared to other youth groups (Chan et al, 2021). Panel studies between 2009 and 2020 found a negative impact of CBs on the mental health of the general population: more potential depression during 2019-20 (11-12% respondents with high symptoms of depression) and 2017 (6-5% mobilizations compared to previous years; 1-9% during 2009-14).…”
Section: Conclusion: Limitations Of Collective Action Frames As Expla...mentioning
confidence: 99%
“…On the other hand, a Swiss longitudinal study using panel data found that intention to participate in demonstrations slightly predicted negative emotions, and intention to participate in strikes decreased positive emotions, as well as that emotional distress predicted intention to participate in CB (Lindholm, 2020). Crosssectional, 3-month and 1-year follow-up studies have found that participating in unsuccessful SM demonstrations (such as the Umbrella movement in Hong Kong) while inducing positive emotions at the climatic moment of the CBs, causes a decrease in these when the movement fails (Hou and Bonano, 2018;Chan et al, 2021;Fung, 2022). These results suggest that participation in SMs, particularly unsuccessful ones, has an emotional cost, although in the case of successful ones, this is compensated by improvements in the emotional balance.…”
Section: Conclusion: Limitations Of Collective Action Frames As Expla...mentioning
confidence: 99%
“…Collective actions are a key aspect towards social change ( Thomas and Louis, 2013 ). From student manifestations against tuition fees in Germany ( Tausch et al, 2011 ), to social protests in Armenia during the Velvet Revolution ( Burrows et al, 2022 ), the Egyptian revolution ( Sadowski et al, 2017 ), and the Chilean social outburst of 2019 ( Castro-Abril et al, 2021 ; Gerber et al, 2023 ) collective actions have occurred throughout history and all around the world. However, although collective actions are directed towards goals, they rarely achieve them right away ( Louis et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%